Characterisation and genotyping of methicillin-resistant staphylococcus aureus isolates from a tertiary healthcare centre in Ogun state Nigeria - Ehlers, M.M. (Marthie Magdaleen) (2026)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2015.